Petrogenesis and geochronology of granitoids from the Tseel terrane, SW Mongolia - Ulziiburen Burenjargal; Atsushi Okamoto; Noriyoshi Tsuchiya; Kenji Horie; Tomokazu Hokada; Dieter Mader; Christian Koeberl (Geological Issues, 2023)
In this study, geochemistry and geochronology of granitoids in the Tseel area of the Tseel terrane, SW Mongolia, are examined to constrain the tectonic setting for the igneous activity and its relation to metamorphism. The massive of granitoid in the central part of the Tseel area was dated to be 281.3 ± 1.1 Ma. Comparison with the previous geochronological studies on metapelites suggests that these granitoid intrusions occurred after the main metamorphic events. In the Tseel area, granitoids yield various ages including the Devonian and Permian ages. These granitoids show geochemical signatures for subduction-related magmatism, including the concave and negative anomalies of Eu in the REE pattern and enriched LILEs. The similarity in the geochemical signature between the Tseel terrane and the Chinese Altai implies that these regions are the same arc related system, which extended from SW Mongolia to Chinese Altai.